The impact of nutritional status and dietary intake on children's exposure to hazardous substances in food - Aurora, Wahyu Indah Dewi; Darmawan, Armaidi; Kusdiyah, Erny; Suzan, Raihanah; Syauqy, Ahmad; Gading, Patrick William (Department of Nutrition Science, Faculty of Medicine, Universitas Diponegoro, 2025)
Introduction: Exposure to harmful substances in food is a significant factor contributing to stunting and nutritional problems in children, as it impacts their growth and development. While healthy diets are well-documented, direct links between dietary intake and harmful substance exposure are less explored. This study investigates key risk factors influencing such exposure in children.Objectives: This study aimed to analyses the impact of nutritional status, dietary intake, and exposure to harmful substances in children.Materials And Methods: A cross-sectional study involving 780 children in 30 elementary Schools, collected data on dietary intake, nutritional status, and laboratory testing for harmful substances like borax, formalin, Rhodamine B, and cyclamate using Qualitative Test Kit. Food samples were obtained from school vendors and commonly consumed items. Data were analysed using Chi-Square tests and binary logistic regression to assess the relationships between variables.Results: Among the children, 50% were aged 8–9 years, and 53.8% were female. Most had good nutritional status (69.2%), and 88.2% had sufficient dietary intake. However, 69.1% were exposed to harmful substances in food. Poor nutritional status increased exposure risk by 3.11 times (PR = 3.11; 95% CI: 1.75 - 5.51; p = 0.000), and insufficient dietary intake raised it by 13.26 times (PR = 13.26; 95% CI: 8.37 - 21.02; p = 0.000).Conclusion: A child’s nutrition and food safety are deeply connected. Poor nutrition makes children more susceptible to harmful substances, highlighting the importance of ensuring both a healthy diet and stricter food safety measures. By prioritizing better nutrition and safer food choices, we can help protect children's health and support their growth.